Spatial Integration and Geographic Modernization : Review of Theories and Synthesis - Comtois, Claude (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1986)
The main concern of this paper is to combine the process of spatial integration with that of geographic modernization. Spatial integration is defined as a process by which the combination of centrality and marginality forms the basic contradiction of the spatial dialectic: the spatial struggle. Whereas geographic modernization is a process related to the development and the mutual transformation of terrestrial space and socio-economic formations leading to new spatial forms. The paper argues that the underlying mechanism of spatial integration is the geographic transfer of social surplus product. Whereas geographic modernization is the outcome of the geographic mobility of productive forces.